The European Respiratory Society's 10 Principles for Lung Health. Issue 5 (29th November 2018) - Horváth, Ildikó; Barry, Maeve; Brusselle, Guy; Burghuber, Otto Chris; Bush, Andrew; Robalo Cordeiro, Carlos; Gaga, Mina; Gratziou, Christina; Saraiva, Isabel; Stolz, Daiana; Troosters, Thierry; Welte, Tobias; et al.
June 2017 saw the annual European Respiratory Society (ERS) Presidential Summit in Ghent, Belgium. Entitled "A public health approach to respiratory health", the summit brought together respiratory specialists and public health voices to discuss what respiratory health now means in terms of public health [1]. In looking at public health and disease prevention, the summit took up themes from the The European Lung White Book [2] with debate centred on public health pyramid for respiratory health [3], while drawing on approaches from other disease areas [4]. With the ERS 10 Principles for Lung Health, @ERSTalk proposes a call to action to improve respiratory health and invites all stakeholders (politicians, policy makers, patients and the public) to support it http://ow.ly/9dW730mkhZu